The constraints of Administrative Readiness in the process to the Regional General Service Agency of Public Health Center in Anambas Islands Regency - ANDRI PURNOMO; Sutopo Patria Jati; Ayun Sriatmi (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
ABSTRAKLatar Belakang: Puskesmas BLUD memberikan poin lebih dalam hal keleluasaan mengelola keuangan. Proses pengajuan BLUD Puskesmas selama ini masih terkendala dengan kelengkapan persyaratan yang dianggap belum memenuhi ketentuan. Dari tiga persyaratan hanya persyaratan administratif yang belum dipenuhi. Penelitian ini bertujuan menganalisis kendala kesiapan dalam pemenuhan persyaratan administratif menuju Puskesmas BLUD.Metode: Merupakan penelitian deskriptif dengan pendekatan kualitatif. Lokasi penelitian di Puskesmas Palmatak dan Puskesmas Tarempa dengan alasan kedua puskesmas mempunyai cakupan layanan terbanyak, jumlah kunjungan terbanyak dan sebagai Puskesmas penerima kapitasi terbesar. Subjek penelitian Kepala Puskesmas dan Kepala TU sebagai informan utama dengan informan triangulasi Kepala Dinkes PPKB dan Kabid Pelayanan Kesehatan. Pengumpulan data dengan wawancara mendalam dan telaah dokumen. Data yang terkumpul dianalisis dengan metode analisis isi.Hasil: Puskesmas di Kabupaten Kepulauan Anambas terkendala dengan kemampuan melengkapi persyaratan administratif sehingga dokumen tidak bisa dikumpulkan dalam waktu yang cepat dan lengkap. Dari 6 dokumen yang harus dikumpulkan, Puskesmas Palmatak mengumpulkan 4 dokumen dan Puskesmas Tarempa 2 dokumen. Dokumen yang tidak dikumpulkan oleh kedua Puskesmas adalah dokumen surat pernyataan kesanggupan meningkatkan kinerja dan dokumen laporan audit terakhir. Sementara untuk dokumen pola tata kelola, rencana strategi bisnis dan laporan keuangan pokok masih belum lengkap, sedangkan dokumen standar pelayanan minimal sudah dipenuhi. Kendala Puskesmas dalam melengkapi persyaratan administratif karena kurangnya motivasi dan lemahnya komunikasi internal Puskesmas. Selain itu pemahaman yang tidak benar tentang peran petugas apalagi dilatarbelakangi karakteristik pendidikan yang berbeda.Simpulan: Puskesmas belum siap menjadi BLUD. Perlu koordinasi intensif antara Puskesmas dan Dinkes PPKB melalui konsultasi secara rutin dan terjadwal.Kata Kunci: Kendala, persyaratan administratif, Badan Layanan Umum DaerahABSTRACTTitle: The constraints of Administrative Readiness in the process to the Regional General Service Agency of Public Health Center in Anambas Islands RegencyBackground: The financial managing in the Regional General Service Agency of public health center were more flexibility. The submission process of the Regional General Service Agency of public health center stilll constrained by incompleteness of requirements of the provisions. There was only administrative requirement from three requirnents that have not been fullfill. This research aims to analyze the constraints of readiness in fulfilling the administrative requirements towards the Regional General Service Agency of public health center.Method: It is a descriptive research with a qualitative approach. The location of this research in Palmatak Public health center and Tarempa Public health center which has the most service coverage, the largest number of visits and as the largest capitation of recipient's Public health center. The main informant of this research were head of Public health center and head of administration. The triangulation informants of this research were the head of Health Office in Population Control and Family Planning and the head of Health Service. The data collected by in-depth interviews and document study. This Collected data is analyzed by methods content analysis.Result: The Public health center in the Anambas Islands District was constrained by the ability to completed the administrative requirements. It caused the documents could not be collected timely and completly. From the 6 documents must be gathered, Palmatak Public health center just collected 4 documents and Tarempa Public health center just collected 2 documents. The documents did not collected by both public health centres were the ability to improve the performance document and the latest audit report document. Mainwhile, the governance documents, the business strategy plan and the underlying financial statements were still incomplete but the standard minimal service document was fullfill. The Problem of Public health center in completing the administrative requirement caused by the weak of motivation and internal communication in public health center. Besides, the incorrect understanding of employee role because of different educational characteristics. Conclusion: The Public health center is not ready to become a regional General Service Agency. It needs intensive coordination between the Public health center and the Health Department of Population and Family Planning through regular and scheduled consultation.Keywords: Constraints, administrative requirements, regional public service agency